Parents, schools and the twenty-first-century state: comparative perspectives. Issue 3 (2nd July 2020) - Proctor, Helen; Roch, Anna; Breidenstein, Georg; Forsey, Martin
ABSTRACT: This article introduces a collection of papers comprising the special issue, Competing interests: Parents, Schools and Nation States . Drawing on the seven papers in the collection, and situating them in recent developments in the sociological field, the article discusses globally shifting relations between families, schools and the state across a range of nations in the late twentieth and early twenty-first centuries (Australia, Germany, India, Norway, Singapore, Sweden, USA). The article proposes that the school is a crucial site for relations between family and state, and argues that a significant focus of the material and occupational investment of contemporary parents is the formal education of their children, re-shaping not only the relationship between parents and schools but also the nature of parenthood itself. In the contemporary context of global neoliberal education reform, parents are analysed both as local actors in schools and as subjects of national and international policy regimes.